2013
DOI: 10.3846/16111699.2011.638668
|View full text |Cite
|
Sign up to set email alerts
|

The Eu Apportionment Formula: Insights From a Business Case

Abstract: In this paper we use firm level data from a listed multinational to investigate how several designs for the Common Consolidated Corporate Tax Base (CCCTB) formula could affect the allocation of the consolidated tax base. The design is relevant in the light of member states’ concern for protecting their tax revenues, as well as for the multinational companies’ tax minimizing possibilities. Moreover, it plays an important role in achieving an efficient and simple tax system. Simulating different apportionment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 5 publications
1
36
0
Order By: Relevance
“…Altshuler and Grubert (2010) stated that the general problem with the FA is the potential asymmetry between the determinants of taxable income and the factors that enter the FA. Roggeman et al (2013) studied several configurations of the FA, concluding that to create an efficient FA and reduce multinational companies' incentive to profit shifting, more factors with more equal weights should be included. McLure (1981) argued that the FA methodology largely transforms the corporate income tax into a direct tax on the factors applied in the FA.…”
Section: Composition and Factors Of Fa Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Altshuler and Grubert (2010) stated that the general problem with the FA is the potential asymmetry between the determinants of taxable income and the factors that enter the FA. Roggeman et al (2013) studied several configurations of the FA, concluding that to create an efficient FA and reduce multinational companies' incentive to profit shifting, more factors with more equal weights should be included. McLure (1981) argued that the FA methodology largely transforms the corporate income tax into a direct tax on the factors applied in the FA.…”
Section: Composition and Factors Of Fa Methodologymentioning
confidence: 99%
“…McLure (2000) addressed the choice of FA factors with regard to digitalized economy based on new types of value-creating assets and problematic application of the traditional nexus. Roggeman et al (2012) discussed and empirically tested the inclusion of intangible assets in the FA. Later, Martins and Taborda (2022) debated the recognition of intangible assets and concluded that they should, in principle, be introduced in the FA.…”
Section: Composition and Factors Of Fa Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The consideration of demand in a formulaic profit distribution goes back to Musgrave (1972). Roggeman et al (2013) simulate the splitting results of different formular designs. Lessons from the Canadian example are presented by Mintz (2004, S. 222 f.).…”
Section: Literature Overviewmentioning
confidence: 99%